2020
DOI: 10.1136/vetreccr-2020-001281
|View full text |Cite
|
Sign up to set email alerts
|

Development of a lateral ultrasound‐guided approach for the radial, ulnar, median and musculocutaneous (RUMM) nerve block in a calf undergoing surgical fixation of the antebrachium

Abstract: A 26-day-old Pustertaler Sprinzer calf was referred to the ruminant clinic of the Veterinary University of Vienna for internal fixation of a suspected traumatic radius–ulnar fracture of the left forelimb. Preanaesthetic medication consisted of xylazine 0.06 mg/kg and ketamine 6 mg/kg intramuscularly, followed by induction of anaesthesia with ketamine 2.7 mg/kg intravenously. Anaesthesia was maintained with isoflurane in oxygen. A modified lateral ultrasound-guided radial, ulnar, median and musculocutaneous (RU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…This report describes a successful desensitisation of the R nerve by a lateral approach and the UMM nerves by a medial approach at mid‐humeral level, guided by ultrasound in calves. A similar approach was successfully applied in an alpaca undergoing radial fracture repair, 10 while a lateral approach to both R and UMM nerves has been reported in one calf 9 . There are no further reports regarding use of RUMM block in ruminants, and the potential advantages or disadvantages of each technique remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This report describes a successful desensitisation of the R nerve by a lateral approach and the UMM nerves by a medial approach at mid‐humeral level, guided by ultrasound in calves. A similar approach was successfully applied in an alpaca undergoing radial fracture repair, 10 while a lateral approach to both R and UMM nerves has been reported in one calf 9 . There are no further reports regarding use of RUMM block in ruminants, and the potential advantages or disadvantages of each technique remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was successfully applied in an alpaca undergoing radial fracture repair, 10 while a lateral approach to both R and UMM nerves has been reported in one calf. 9 There are no further reports regarding use of RUMM block in ruminants, and the potential advantages or disadvantages of each technique remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deze techniek zorgt voor desensitisatie van het onderste lidmaat distaal van de elleboog. Deze techniek werd reeds gebruikt voor ingrepen zoals tenectomie bij kalveren of bij een radiusfractuur bij alpaca's (Alonso et al, 2023;Trujanovic et al, 2020). Om de optimale lokalisering van de zenuw te bekomen, werd deze block zoals in de voorliggende studie onder echobegeleiding uitgevoerd.…”
Section: Discussieunclassified
“…Superb microvascular imaging (SMI) is a new type of imaging technology that detects human blood flow and displays the flow in a visual form, which can diagnose the vascular diseases of patients directly and accurately. It has been reported that the sensitivity and specificity of SMI in the detection and diagnosis of small renal tumors are relatively high, which can greatly improve the detection rate and accuracy of small renal tumors [7][8][9]. To further study the application value of color Doppler ultrasound combined with SMI in the diagnosis of small renal tumors, patients with small renal tumors were selected as the research objects to compare the specificity, sensitivity, positive and negative detection results, and detection accuracy between color Doppler ultrasound and SMI combined with color Doppler ultrasound, aiming to clarify the application value and diagnostic effect of color Doppler ultrasound combined with SMI in clinical practice, with details reported as below.…”
Section: Introductionmentioning
confidence: 99%